Calcium Alginate-Caged Multiwalled Carbon Nanotubes Dispersive Microsolid Phase Extraction Combined With Gas Chromatography-Flame Ionization Detection for the Determination of Polycyclic Aromatic Hydrocarbons in Water Samples. (24th November 2017) - Abboud, Ayad Sami; Sanagi, Mohd Marsin; Ibrahim, Wan Aini Wan; Keyon, Aemi S Abdul; Aboul-Enein, Hassan Y
Abstract: In this study, caged calcium alginate-caged multiwalled carbon nanotubes dispersive microsolid phase extraction was described for the first time for the extraction of polycyclic aromatic hydrocarbons (PAHs) from water samples prior to gas chromatographic analysis. Fluorene, phenanthrene and fluoranthene were selected as model compounds. The caged calcium alginate-caged multiwalled carbon nanotubes was characterized by Fourier transform infrared spectroscopy, scanning electron microscopy and thermal gravimetry analyses. The effective parameters namely desorption solvent, solvent volume, extraction time, desorption time, the mass of adsorbent and sample volume were optimized. Under the optimum extraction conditions, the developed method showed good linearity in the range of 0.5–50 ng mL −1 ( R 2 ≥ 0.996), low limits of detection and quantification (0.42–0.22 ng mL −1 ) (0.73–1.38 ng mL −1 ) respectively, good relative recoveries (71.2–104.2%) and reproducibility (RSD 1.8–12.4%, n = 3) for the studied PAHs in water sample. With high enrichment factor (1, 000), short extraction time (<30 min), low amounts of adsorbent (100 mg) and low amounts of solvent (0.1 mol) have proven that the microsolid phase extraction method based on calcium alginate-caged multiwalled carbon nanotubes are environmentally friendly and convenient extraction method to use as an alternative adsorbent in the simultaneous preconcentration of PAHs from environmental water samples.